ANALISIS MAKRO PEMBIAYAAN PENDIDIKAN DI SMPN 1 ANGGANA - Ratnawati, Eny; Rachim, Abd.; Mulawarman, Widyatmike Gede; Warman, Warman (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This study aims to conduct an in-depth analysis of the management of School Operational Assistance (BOS) funds at Anggana 1 State Junior High School. The background of this study is based on the importance of transparency and accountability in the use of BOS funds to support school operations and improve the quality of education. The main focus of this study is to examine how the BOS fund management process, from planning to accountability, is implemented at Anggana 1 State Junior High School. To achieve this goal, this study uses a qualitative-descriptive approach. Important steps in this study include collecting primary data through in-depth interviews with the principal, school treasurer, and several other key informants who are directly involved in the management of BOS funds. Secondary data is also collected through a review of related documents. Furthermore, data analysis is carried out comprehensively by focusing on three main aspects of BOS fund management, namely the budget planning stage, the budget implementation or use stage, and the accountability stage for the use of these funds. The results of the study indicate that in general, the management of BOS funds at SMPN 1 Anggana has been carried out in accordance with the provisions stipulated in the Regulation of the Minister of Education, Culture, Research, and Technology (Permendikbudristek) Number 12 of 2022. One important finding is the implementation of the School Financial Management Application (ATKP) system in the implementation of the use of BOS funds, where no cash payment transactions were found. In addition, the process of accountability for the use of BOS funds has also been carried out optimally by the school. However, this study also identified several obstacles faced, especially related to the delay in the disbursement of BOS funds from the district government. This delay has an impact on the smooth implementation of activities that have been budgeted by the school. The main conclusion of this study is that SMPN 1 Anggana has made efforts to manage BOS funds well and in accordance with regulations, but its effectiveness can be further improved by overcoming external obstacles such as delays in the disbursement of funds. ABSTRAKPenelitian ini bertujuan untuk melakukan analisis mendalam terhadap pengelolaan dana Bantuan Operasional Sekolah (BOS) di Sekolah Menengah Pertama Negeri 1 Anggana. Latar belakang penelitian ini didasari oleh pentingnya transparansi dan akuntabilitas dalam penggunaan dana BOS untuk mendukung operasional sekolah dan peningkatan mutu pendidikan. Fokus utama penelitian ini adalah untuk mengkaji bagaimana proses pengelolaan dana BOS, mulai dari perencanaan hingga pertanggungjawaban, dilaksanakan di SMPN 1 Anggana. Untuk mencapai tujuan tersebut, penelitian ini menggunakan pendekatan kualitatif-deskriptif. Langkah-langkah penting dalam penelitian ini meliputi pengumpulan data primer melalui wawancara mendalam dengan kepala sekolah, bendahara sekolah, serta beberapa informan kunci lainnya yang terlibat langsung dalam pengelolaan dana BOS. Data sekunder juga dikumpulkan melalui telaah dokumen terkait. Selanjutnya, analisis data dilakukan secara komprehensif dengan memfokuskan pada tiga aspek utama pengelolaan dana BOS, yaitu tahap perencanaan anggaran, tahap pelaksanaan atau penggunaan anggaran, dan tahap pertanggungjawaban atas penggunaan dana tersebut. Hasil penelitian menunjukkan bahwa secara garis besar, pengelolaan dana BOS di SMPN 1 Anggana telah berjalan sesuai dengan ketentuan yang diatur dalam Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi (Permendikbudristek) Nomor 1 2 Tahun 2022. Salah satu temuan penting adalah implementasi sistem Aplikasi Tata Kelola Keuangan Sekolah (ATKP) dalam pelaksanaan penggunaan dana BOS, di mana tidak ditemukan adanya transaksi pembayaran secara tunai (cash). Selain itu, proses pertanggungjawaban penggunaan dana BOS juga telah dilaksanakan secara maksimal oleh pihak sekolah. Meskipun demikian, penelitian ini juga mengidentifikasi beberapa kendala yang dihadapi, terutama terkait dengan keterlambatan proses pencairan dana BOS dari pihak pemerintah kabupaten. Keterlambatan ini berdampak pada kelancaran pelaksanaan kegiatan-kegiatan yang telah dianggarkan oleh sekolah. Simpulan utama dari penelitian ini adalah bahwa SMPN 1 Anggana telah berupaya mengelola dana BOS dengan baik dan sesuai regulasi, namun efektivitasnya dapat lebih ditingkatkan dengan mengatasi kendala eksternal seperti keterlambatan pencairan dana.